DIALOGUE OF CIVILIZATIONS: THE INFLUENCE OF THE OTTOMAN EMPIRE ON MODERN EUROPE - Sarkawt Tawfeeq Sidiq (Senarai: Journal of Islamic Heritage and Civilization, 2026)
This study examines the multidimensional influence of the Ottoman Empire (1299-1922) on European political, economic, intellectual, and cultural development through systematic analysis of historical documents and secondary literature. Challenging traditional historiography that portrays the Empire solely as Europe's antagonist, this research demonstrates that Ottoman-European relations constituted a productive dialogue that fundamentally shaped European modernity. The analysis reveals three primary mechanisms of influence: (1) Ottoman military power catalyzed European state centralization and the Military Revolution; (2) Ottoman control of Eastern trade routes stimulated the Age of Exploration and early capitalism; (3) Ottoman governance models, particularly regarding religious pluralism and merit-based administration, provided alternative frameworks that informed Enlightenment debates. Specific case studies document how Ottoman diplomatic and commercial support enabled the survival of France, England, and Holland against Habsburg dominance, while Ottoman scientific and medical knowledge—exemplified by smallpox inoculation practices—directly advanced European public health. The study concludes that understanding European modernity requires recognizing the Ottoman Empire not as peripheral adversary but as central interlocutor whose presence shaped the continent's institutional, economic, and intellectual architecture. The main research questions are: (1) In what ways did the Ottoman Empire shape the growth of modern Europe? (2) What was the nature of Ottoman-European interaction beyond the traditional conflict narrative? (3) How did the Ottoman Empire help European civilization change and adapt?